Effects of Exercise on the Skin Epithelial Barrier of Young Elite Athletes-Swimming Comparatively to Non-Water Sports Training Session - Paciencia, I (2021)
The benefits of swimming have been extensively assessed. However, swimming pools contain chlorine and other irritating chemicals that may induce contact dermatitis. To evaluate the effect of a swimming training session on transepidermal water loss (TWEL) in swimmers compared to football players, elite swimmers and football players were invited to participate (58 athletes) in the study, where TEWL was measured before, immediately after, and 30 min after a 2 h training session. The probe was held on the dorsum of the hand, volar forearm, and on the antecubital flexure for 1 min. The volar forearm, antecubital flexure, and hand dorsum showed a significant increase in TEWL in swimmers in both measurements after training compared to baseline (p < 0.001). In football players, an increase in TEWL was observed on the hands' dorsum between baseline and after training measurements. The variations on TEWL levels before and immediately after the training session were higher among swimmers on the volar forearm (p = 0.002) and antecubital flexure (p = 0.019). Our findings support the effect of the training environment-swimming pool versus outdoor sports-on the skin barrier function, with an increase of transepidermal water loss immediately after exercise. Exposure to a swimming pool environment in a 2 h training session may lead to changes in skin barrier function.